Pertimbangan Hakim dalam Memutuskan Permohonan Afwezigheid PT Bentoel Internasional Investama - Yundha Rachmawati; Anjar Sri Ciptorukmi Nugraheni (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This paper intends to investigate the factors taken into account by the judge in determining the absence in the case of PT Bentoel Internasional Investama at the South Jakarta District Court, analyze the procedures for managing assets whose owners are absent based on the applicable regulations in Indonesia, and investigate the compliance of the procedures for managing shares as afwezidheid assets in the case of PT Bentoel Internasional Investama conducted by the Jakarta Balai Harta Peninggalan (BHP) with the regulations in Indonesia. This study is an empirical legal one using a qualitative methodology. Primary and secondary data are the forms of the information applied. Data collecting methods used are literature reviews and interviews. The interviews were carried out applying flexible topic development based on interview rules. This work employs approaches of descriptive analysis. According to the findings of this investigation, the judge decided on the absence petition of PT Bentoel Internasional Investama based on pertinent legal reasons, legal precedents, and facts provided by the petitioner in view of Under the Indonesian Civil Code, Regulation of the Minister of Law and Human Rights of the Republic of Indonesia No. 27 of 2013, and Regulation of the Minister of Law and Human Rights No. M.02-HT.05.10 of 2005 the process for managing shares as assets whose owners are absent (boedel afwezigheid) by the Jakarta BHP is governed. Regarding PT Bentoel Internasional Investama, the management of afwezigheid shares was done in line with Indonesian laws by means of an application to the South Jakarta District Court, which designated the Jakarta BHP as the legal administrator. This process complies with Articles 463–465 of the Civil Code and Standard Operating Procedure (SOP) Number AHU.UM.01.01-235, including public notification of share status in mass media, management, recording, safekeeping of collective share certificates, and BHP reports share management to the Supreme Audit Agency (BPK) and the Attorney General's Office and handles official and material tests. Since no objections were found, the Jakarta BHP filed none.